"Contribution à l’étude de l’efficacité de l’irrigation au goutte à goutte dans la wilaya d’El-Oued -COMPARAISON ENTRE METHODE GOUT A GOUT ET METHODE PIVOT-" - بريبش, بدر; حوه, عادل; مساعيد, جلال (Université d'El Oued, 2022)
"The rational use of water in agriculture involves knowing the water needs of crops through an appropriate assessment of the criteria governing the environmental conditions, and in particular through the efficient use of this water through the choice of irrigation systems. In this context, our work focuses on the study of the drip irrigation system in the region of Oued Souf. Since it began to spread across the world, drip irrigation technology has established itself as a global agricultural technology, expanding the horizons of modern agriculture. Drip technology also improved the efficiency of water use in irrigation and began to introduce and develop irrigation and integrated water and fertilizer distribution. We found through this study that 93% of cultivated land is irrigated, of which 32.46% is drip of this area. This is to save water and labor and improve performance, economy and profit." "يتضمن الاستخدام العقلاني للمياه في الزراعة معرفة الاحتياجات المائية للمحاصيل من خلال التقييم المناسب للمعايير التي تنظم ظروف البيئة، وخاصة من خلال الاستخدام الفعال لهذه المياه عن طريق اختيار أنظمة الري. في هذا السياق، يركز عملنا على دراسة نظام الري بالتنقيط في منطقة وادي سوف، فمنذ بداية توزيعها في جميع أنحاء العالم، أكدت تقنية الري بالتنقيط نفسها على أنها تقنية زراعية عالمية، حيث تعمل على توسيع آفاق الزراعة الحديثة. كما حسنت تقنية التنقيط من كفاءة استخدام المياه في الري وبدأت في إدخال وتطوير الري والتوزيع المتكامل للمياه والأسمدة. وجدنا من خلال هذا دراستنا أن 93٪ من الأراضي المزروعة المسقية، منها 32.46٪ الري بالتنقيط من هذه المساحة. وذلك من أجل توفير المياه والعمالة وتحسين الأداء والاقتصاد والربح."
مذكرات ماستر تخصص ري
Keywords: El Oued, irrigation, drip, groundwater.; الوادي، الري، الري بالتنقيط، المياه الجوفية